2014
DOI: 10.1039/c3gc42401d
|View full text |Cite
|
Sign up to set email alerts
|

Understanding pretreatment efficacy of four cholinium and imidazolium ionic liquids by chemistry and computation

Abstract: Understanding specific combinations of cations and anions of ionic liquids for biomass pretreatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
146
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 148 publications
(169 citation statements)
references
References 39 publications
16
146
2
Order By: Relevance
“…Taken together, compositional analysis and molecular modeling data suggest that lignin removal efficiency is a better indicator of switchgrass pretreatment performance compared with β and net basicity values when comparing benzylammonium and furfurylammonium ILs to those of imidazolium. These results are in agreement with previous findings in our group whereby cholinederived ILs with high lignin removal efficiency and high experimentally obtained β values resulted in high sugar yields across a broad range of pretreatment temperatures (42). It is thought that the mechanism of action of the lignin-and hemicellulose-derived ILs is therefore more akin to other biologically derived ILs, such as ILs prepared from choline.…”
Section: Compositional Analysis Of Untreated and Pretreated Switchgrasssupporting
confidence: 83%
See 2 more Smart Citations
“…Taken together, compositional analysis and molecular modeling data suggest that lignin removal efficiency is a better indicator of switchgrass pretreatment performance compared with β and net basicity values when comparing benzylammonium and furfurylammonium ILs to those of imidazolium. These results are in agreement with previous findings in our group whereby cholinederived ILs with high lignin removal efficiency and high experimentally obtained β values resulted in high sugar yields across a broad range of pretreatment temperatures (42). It is thought that the mechanism of action of the lignin-and hemicellulose-derived ILs is therefore more akin to other biologically derived ILs, such as ILs prepared from choline.…”
Section: Compositional Analysis Of Untreated and Pretreated Switchgrasssupporting
confidence: 83%
“…A slight shielding of the methylene carbons in the α position were also observed when converting the amine δ = 45.9 ppm (2C) and δ = 54.8 ppm (1C) to the IL δ = 45.3 ppm (2C) and δ = 54.6 ppm (1C PO 4 ] were also selected based on their subtle differences in polarity and substituent effects. The polarity of an IL has been correlated with its ability to solubilize both lignin (42,43) and cellulose (44)(45)(46) PO 4 ] were used to dissect the role of these substituents on the relative acidity of the cation and relate these effects to biomass pretreatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hou et al (2012) 18 found choline-based ILs to be effective pretreatment solvents with high polysaccharide digestibility and sugar yields. Sun et al 19 reported that [Lys] anions provided greater delignification (70-80% vs. 16-50%) and higher glucose yields (78-96% vs. 56-90%) compared to [OAc] anions. ILs containing the lysinate anion afforded greater delignification and higher glucose yields than other anions such as carboxyl, hydroxyl, and aromatic groups 26 .…”
Section: Introductionmentioning
confidence: 99%
“…A variety of ILs, including 1-ethyl 1-methylimidazolium acetate ([C 2 MIM][OAc]) [14][15][16] , 1-ethyl 1-methylimidazolium chloride ([C 2 MIM][Cl]) 17 , and cholinium lysinate ([Ch][Lys]) [18][19][20] , have been explored for the pretreatment of various lignocellulosic biomass feedstocks including corn stover 14,[21][22] , switchgrass 9,12 , pine 23 , miscanthus 15,24 and mixed feedstock 25 . Choline-based ILs, sometimes referred to as "bionic liquids" because they are bio-derived, are particularly attractive because they can be produced using cheaper raw materials and simpler synthesis methods than [C 2 MIM]-based ILs 20 .…”
Section: Introductionmentioning
confidence: 99%